Two for the price of one? On additionality effects of R&D subsidies: A comparison between Flanders and Germany - Kris Aerts; Tobias Schmidt (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2006)
In this paper we empirically test whether public R&D subsidies crowd out private R&D investment in Flanders and Germany, using firm level data from the Flemish and German part of the Community Innovation survey (CIS III and IV). Both the non-parametric matching estimator and the conditional difference-in-difference estimator with repeated cross-sections (CDiDRCS) clearly indicate that the crowding-out hypothesis can be rejected: funded firms are significantly more R&D active than non-funded firms. In the domain of additionality effects of R&D subsidies, this paper is the first to apply the CDiDRCS method.
Keywords: O38; H50; C21; C14; 330; R&D; Subsidies; Policy Evaluation; Conditional Difference-in-Difference